KARAKTERISTIK USAHATANI TEMBAKAU DI DAERAH PINGGIRAN HUTAN - Okky Dwiartono Putro Sabtono; M Gunardi Judawinata (Universitas Galuh, 2022)
Tobacco is one of the potential estate crops commodity because of the large amount of consumer within the productive age group. In recent years, Bandung District's production of tobacco is increasing and didn’t decrease it’s land area. Furthermore, Cicalengka Sub-district productivity is in the top five of Bandung District. So, the Cicalengka Sub-district can be assumed potential in tobacco farming. Based on the observation in Cijaha, Tanjungwangi Village there is a phenomenon where farmer leaving their profession to non-farming related profession that resulted from good accessibility to the industries central and to the city. However, there are some that still farming tobacco. The purpose of this research is to find out the farmer’s characteristic, their cultivation system, and profitability of the farmers in Cijaha. The research method used is the qualitative method with a case study approach. The analysis of this research was using are characteristic theory, tobacco cultivation technique, and farming feasibility with using snowball technique for sample selection. The tobacco farmer in Cijaha are categorized in non-productive age group, their education finished until elementary school, their number of dependents are low. The farmers are categorized as small-scale farmer, their land tenure are self-owned and rent, and the tobacco farmers are not motivated to expand their tobacco farming. Their method for cultivating tobacco is in accordance with expert's method, and tobacco farming in Cijaha, Tanjungwangi Village are incured losses and not feasible to expand further.